1996
DOI: 10.1007/bf01877058
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of pure and hybrid willows to isolates ofMelampsora epitea rust

Abstract: Pure species and F1 hybrid families of Salix viminalis and S. dasyclados were tested for resistance to four single uredinium isolates of Melampsora rust in laboratory experiments using excised leaves. Rust isolates were derived from: S. viminalis, S. dasyclados, a S. viminalis x triandra hybrid, and S. daphnoides. Incidence of infection, number of uredinia per leaf, and numbers of spores per uredinium were measured. As expected, the isolate from S. daphnoides did not infect any of the willow species or hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Fritz, Nichols-Orians, and Brunsfeld (1994) proposed four hypotheses for the responses of hybrids to herbivores: hybrid resistance, hybrid susceptibility, additivity, and dominance. Other studies have demonstrated that the response of hybrids to pathogens may follow similar patterns (Strauss, 1994;Fritz et al, 1996;Hjältén, 1998). Whether all of these hybrid responses are widespread in natural systems, however, is not clear, particularly for pathogens.…”
mentioning
confidence: 91%
“…Fritz, Nichols-Orians, and Brunsfeld (1994) proposed four hypotheses for the responses of hybrids to herbivores: hybrid resistance, hybrid susceptibility, additivity, and dominance. Other studies have demonstrated that the response of hybrids to pathogens may follow similar patterns (Strauss, 1994;Fritz et al, 1996;Hjältén, 1998). Whether all of these hybrid responses are widespread in natural systems, however, is not clear, particularly for pathogens.…”
mentioning
confidence: 91%
“…In comparison with research on rust resistance in poplars, very limited work has been done on the genetics of rust resistance in willows. Previously, Gullberg & Ryttman (1993), Fritz et al. (1996) and Johansson & Alström (2000) examined hybrids within and between S. viminalis and S. dasyclados.…”
Section: Discussionmentioning
confidence: 99%
“…In intraspecific hybrids of S. viminalis , Gullberg & Ryttman (1993) found considerable additive variation in field resistance to rust in Sweden. Fritz et al. (1996) tested intra‐ and interspecific F 1 hybrids of S. viminalis and S. dasyclados (syn.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation